Curriculum Readiness and Program Evaluation In Implementing Indonesian National Qualifications Framework Curriculum (KKNI) - F Fauzan; Asep Ediana Latip (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract The purpose of this study is to determine the study program readiness in State Islamic University (UIN) Jakarta in implementing KKNI based curriculum. It can be seen from the availability of the documents course curriculum in UIN Jakarta which consists of 71% of the vision, mission, graduate profile, achievement of learning, the curriculum structure and Semester Lesson Plan (RPS). It also can be evidenced by the quality of the documents that 1) 99% of study programs have developed a vision and mission for the implementation of the curriculum. 2) 77% of study programs have developed a graduate profile according to level 6 of the KKNI based curriculum which is the basis for the development of graduate-level profile. 3) development of learning achievements in environmental studies program UIN Jakarta, 59% of the study programs have been formulated learning achievements which is in accordance with the learning outcomes defined for an undergraduate level. 4) 35% of the curriculum structure of the study program have met KKNI implementation standards. 5) development of Semester Lesson Plan (RPS) program in environmental studies UIN Jakarta, 82% of the Semester Lesson Plan or RPS which is in line with the principles of RPS development expected in the KKNI implementation has been developed by several study programs at UIN Jakarta. Abstrak Penelitian ini bertujuan untuk mengetahui kesiapan program studi di Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta dalam mengimplementasikan Kurikulum berbasis KKNI. Kesiapan tersebut dapat dilihat melalui ketersediaan dokumen kurikulum program studi di UIN Jakarta yang terdiri dari 71% visi, misi, profil lulusan, capaian pembelajaran, Struktur Kurikulum dan Rencana Pembelajaran Semester (RPS). Selain itu, kesiapan program studi dalam mengaplikasikan dapat dibuktikan dari kualitas dokumen, yakni 1) 99% program studi telah mengembangkan visi dan misi untuk pelaksanaan kurikulum. 2)77% program studi telah mengambangkan profil lulusan menurut level 6 Kurikulum berbasis KKNI yang merupakan dasar untuk pengembangan profil lulusan. 3) pengembangan capaian pembelajaran di lingkungan program studi UIN Jakarta, 59% program studi telah merumuskan capaian pembelajaran yang sesuai dengan hasil belajar yang ditetapkan untuk program sarjana. 4) 35% struktur kurikulum program studi telah memenuhi standar pelaksanaan KKNI. 5) pengembangan Rencana Pembelajaran Semester (RPS) program studi di lingkungan UIN Jakarta, 82% dari Rencana Pembelajaran Semester atau RPS yang sejalan dengan prinsip-prinsip pengembangan RPS yang diharapkan dalam pelaksanaan KKNI telah dikembangkan oleh beberapa program studi di UIN Jakarta. How to Cite : Fauzan., Latip A., E. (2015). Curriculum Readiness and Program Evaluation in Implementing Indonesian National Qualifications Framework Curriculum (KKNI).TARBIYA: Journal Of Education In Muslim Society,2(2), 190-203. doi:10.15408/tjems.v2i2.3179. Permalink/DOI:http://dx.doi.org/10.15408/tjems.v2i2.3179